Frequency, manifestations and management of bezoars in ileal pouches. Issue 5 (24th May 2015) - Wu, Xian‐rui; Ashburn, Jean; Shen, Bo
Abstract : Background and Aim: To evaluate the frequency, diagnosis and management of ileal pouch bezoars. Methods: Patients diagnosed with ileal pouch bezoars at the Pouch Center at Cleveland Clinic from 2002 to 2013 were included. Demographic, clinical and endoscopic features, management and outcomes were evaluated. Results: Twelve patients with ileal pouch bezoars were enrolled, including five (0.4%) of 1390 patients with J‐pouch and seven (13.0%) of 54 with continent ileostomy ( P < 0.001). Males accounted for 25% ( n = 3) of the cohort. Mean age at time of detection was 61.5 ± 10.3 years. Of the 12 patients, six (50.0%) had phytobezoars, four (33.3%) had lithobezoars, one (8.3%) had pharmacobezoar and one (8.3%) had a retained‐Jackson‐Pratt drain. Median number of harvested bezoars was one (range: 1–224), and mean diameter was 4.0 ± 2.4 cm. Bezoars were located at the pouch body in eight (66.7%) patients, pouch inlet in two (16.7%), pouch‐anal anastomosis in one (8.3%) and efferent limb in one (8.3%). Ten patients (83.3%) were symptomatic, including seven (58.3%) with partial bowel obstructive symptoms. Eleven patients (91.7%) were initially managed with endoscopic treatment including basket, RothNet ®, mechanical lithotripsy Tripod and snares. After a median of one (1–3) endoscopic therapy, bezoars were successfully removed in seven patients (58.3%). Surgical intervention was required in the remaining five patients (41.7%). Conclusions: Ileal pouch bezoars appeared to be more frequently encountered in patients with continent ileostomies than in those with J‐pouches. Endoscopic management seemed to be effective in some patients, whereas surgical intervention was needed in others.